Recent Advances in Arsenic Research: Significance of Differential Susceptibility and Sustainable Strategies for Mitigation - Tamalika Sanyal; Tamalika Sanyal; Pritha Bhattacharjee; Pritha Bhattacharjee; Somnath Paul; Pritha Bhattacharjee (Frontiers Media S.A., 2020)
Arsenic contamination in drinking water and associated adverse outcomes are one of the major health issues in more than 50 countries worldwide. The scenario is getting even more detrimental with increasing number of affected people and newer sites reported from all over the world. Apart from drinking water, the presence of arsenic has been found in various other dietary sources. Chronic arsenic toxicity affects multiple physiological systems and may cause malignancies leading to death. Exposed individuals, residing in the same area, developed differential dermatological lesion phenotypes and varied susceptibility toward various other arsenic-induced disease risk, even after consuming equivalent amount of arsenic from the similar source, over the same duration of time. Researches so far indicate that differential susceptibility plays an important role in arsenic-induced disease manifestation. In this comprehensive review, we have identified major population-based studies of the last 20 years, indicating possible causes of differential susceptibility emphasizing arsenic methylation capacity, variation in host genome (single nucleotide polymorphism), and individual epigenetic pattern (DNA methylation, histone modification, and miRNA expression). Holistic multidisciplinary strategies need to be implemented with few sustainable yet cost-effective solutions like alternative water source, treatment of arsenic-contaminated water, new adaptations in irrigation system, simple modifications in cooking strategy, and dietary supplementations to combat this menace. Our review focuses on the present perspectives of arsenic research with special emphasis on the probable causes of differential susceptibility toward chronic arsenic toxicity and sustainable remediation strategies.